ANALISIS KINERJA SALURAN DRAINASE JALAN DI PETEMON 4 KELURAHAN PETEMON KECAMATAN SAWAHAN KOTA SURABAYA - R Endro Wibisono; Dwi Prastya Nurcahaya (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
Surabaya City experiences inundation with heights ranging from 10-70 cm with the longest inundation time of about 6 hours. Surabaya City, for Jalan Petemon gg IV, Petemon Subdistrict, Sawahan District, with an inundation area of ​​0.413ha, inundation height 12.407cm, inundation length of 54.667 minutes. These problems are caused by drainage channels caused by man or nature itself. The purpose of this research is to find out the flood and inundation discharge for the next 2 years on Petemon 4, Petemon, Sawahan, Surabaya, to analyze the condition of the existing drainage channels on Petemon 4, Petemon 4, Petemon, Sawahan, Surabaya , to find alternatives for flood and inundation countermeasures for these channels. able to drain the rain discharge well. The research method of calculating the rain discharge design uses the Nakayasu method. So that the results of the 100 year return flood discharge in the Petemon channel are 340,739 m3 / s while for the capacity with dimensions of length 495 m, width of 4.95 m and depth of 2 m.